Proceedings of the Twentieth Annual ACM-SIAM Symposium on Discrete Algorithms 2009
DOI: 10.1137/1.9781611973068.55
|View full text |Cite
|
Sign up to set email alerts
|

The Geometry of Binary Search Trees

Abstract: We present a novel connection between binary search trees (BSTs) and points in the plane satisfying a simple property. Using this correspondence, we achieve the following results: 3. The first proposal for dynamic optimality not based on splay trees. A natural greedy but offline algorithm was presented by Lucas [1988], and independently by Munro [2000], and was conjectured to be an (additive) approximation of the best binary search tree. We show that there exists an equal-cost online algorithm, transforming th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
161
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(161 citation statements)
references
References 14 publications
0
161
0
Order By: Relevance
“…It seems likely that the ways in which this permutation evolves could be captured by a forbidden substructure argument. Haeupler et al proved their algorithm runs in Opn [7] demonstrated that a greedy offline binary search tree could be simulated online using a technique that resembles path compression. Is it possible to prove that this algorithm has logarithmic access time using some forbidden substructure argument?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It seems likely that the ways in which this permutation evolves could be captured by a forbidden substructure argument. Haeupler et al proved their algorithm runs in Opn [7] demonstrated that a greedy offline binary search tree could be simulated online using a technique that resembles path compression. Is it possible to prove that this algorithm has logarithmic access time using some forbidden substructure argument?…”
Section: Discussionmentioning
confidence: 99%
“…The number of type (iii) rotations is at most n since each such rotation reduces the number of nodes on the left path of an inactive block. 7 The number of type (iv) rotations may be bounded inductively. In the analysis below we build an n{B ¢ n{B period-block incidence matrix A, which is initially zero.…”
Section: Sequential Access In Splay Treesmentioning
confidence: 99%
See 2 more Smart Citations
“…An earlier, similar, concept is competitive analysis [12], whose differences from instance optimality are nicely explained in [17]. Instance optimal algorithms have been designed for many other problems, such as manipulating binary search trees [15], approximating the distance from a point to a curve [8], computing the union/intersection of sorted lists [16], finding the convex hull of polygons [9], to mention just a few. The most recent work to our knowledge is [1], which proposes instance optimal algorithms for several computational geometry problems.…”
Section: Problem and Related Workmentioning
confidence: 99%